2016
DOI: 10.4172/2161-0495.1000312
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Red Blood Transfusion as a Successful Erythrocyte Cholinesterase Supplement in Organophosphate Poisoning

Abstract: Despite improvements to standard treatments (atropine, oxime) and intensive care management, the mortality associated with organophosphate (OP) poisoning has not substantially decreased. In this study, we evaluated the role of packed red blood cells (RBCs) transfusion in acute OP poisoning. Patients diagnosed with OP poisoning were included in this prospective study, and then were transfused with packed RBCs stored less than 10 days or 10 to 35 days. Cholinesterase (ChE) level in blood, atropine usage and dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…In severe poisoning, enzyme recovery usually takes about 4 weeks [24]. If the enzyme level remains low for lasts long, it could cause 'rebound' or intermediate syndrome', and might lead to paralysis of respiratory muscle, which increases the mortality rate [25]. In this study, the levels of ChE enzyme activity were assessed upon arrival and three consecutive later days in all three groups (control, al-bumin, and FFP).…”
Section: Discussionmentioning
confidence: 96%
“…In severe poisoning, enzyme recovery usually takes about 4 weeks [24]. If the enzyme level remains low for lasts long, it could cause 'rebound' or intermediate syndrome', and might lead to paralysis of respiratory muscle, which increases the mortality rate [25]. In this study, the levels of ChE enzyme activity were assessed upon arrival and three consecutive later days in all three groups (control, al-bumin, and FFP).…”
Section: Discussionmentioning
confidence: 96%
“…On top of lipid emulsion therapy, we also considered giving packed RBC transfusion because of its potential to restore AChE activity by delivering additional erythrocyte cholinesterase to scavenge circulating OPs and its potential to decrease total atropine requirement especially in our patient who developed toxicity 8 34 35. Two studies showed this effect where the recovery of the measurable AChE level was significantly faster by 10–20 hours and total atropine requirement was significantly lower by 20%–30% among those who received packed RBC transfusion (200–400 mL) 8 29. These studies also showed that transfusion of fresh RBCs which are stored for less than 10 days showed superiority compared with those in longer storage since AChE activity declines with time 29.…”
Section: Discussionmentioning
confidence: 99%
“…A single dose of 21 mL (1.5 mL/kg, 20%) lipid emulsion was given intravenously over 3 min and was followed by 79 mL (5.5 mL/kg) given at 50 mL/hour (full maintenance rate). Transfusion with packed RBC was also requested as a source of additional erythrocyte cholinesterase, which could be the potential target substrate for circulating OPs 6 8. Six hours after the intravenous lipid emulsion therapy ended, she was transfused with a single dose of 140 mL packed RBC (10 mL/kg/dose) given over 4 hours.…”
Section: Treatmentmentioning
confidence: 99%